Construction of biomimetic cell-sheet-engineered periosteum with a double cell sheet to repair calvarial defects of rats - Zhang, Jun; Huang, Yanran; Wang, Yuping; Xu, Jingtao; Huang, Tianji; Luo, Xiaoji (Journal of orthopaedic translation, 2023)
The periosteum plays a crucial role in the development and injury healing process of bone. The purpose of this study was to construct a biomimetic periosteum with a double cell sheet for bone tissue regeneration. In vitro, the human amniotic mesenchymal stem cells (hAMSCs) sheet was first fabricated by adding 50 ​μg/ml ascorbic acid to the cell sheet induction medium. Characterization of the hAMSCs sheet was tested by general observation, microscopic observation, live/dead staining, scanning electron microscopy (SEM) and hematoxylin and eosin (HE) staining. Afterwards, the osteogenic cell sheet and vascular cell sheet were constructed and evaluated by general observation, alkaline phosphatase (ALP) staining, Alizarin Red S staining, SEM, live/dead staining and CD31 immunofluorescent staining for characterization. Then, we prepared the double cell sheet. In vivo, rat calvarial defect model was introduced to verify the regeneration of bone defects treated by different methods. Calvarial defects (diameter: 4 ​mm) were created of Sprague–Dawley rats. The rats were randomly divided into 4 groups: the control group, the osteogenic cell sheet group, the vascular cell sheet group and the double cell sheet group. Macroscopic, micro-CT and histological evaluations of the regenerated bone were performed to assess the treatment results at 8 weeks and 12 weeks after surgery. In vitro, hAMSCs sheet was successfully prepared. The hAMSCs sheet consisted of a large number of live hAMSCs and abundant extracellular matrix (ECM) that secreted by hAMSCs, as evidenced by macroscopic/microscopic observation, live/dead staining, SEM and HE staining. Besides, the osteogenic cell sheet and the vascular cell sheet were successfully prepared, which were verified by general observation, ALP staining, Alizarin Red S staining, SEM and CD31 immunofluorescent staining. In vivo, the macroscopic observation and micro-CT results both demonstrated that the double cell sheet group had better effect on bone regeneration than other groups. In addition, histological assessments indicated that large amounts of new bone had formed in the calvarial defects and more mature collagen in the double cell sheet group. The double cell sheet could promote to repair calvarial defects of rats and accelerate bone regeneration. We successfully constructed a biomimetic cell-sheet-engineered periosteum with a double cell sheet by a simple, low-cost and effective method. This biomimetic periosteum may be a promising therapeutic strategy for the treatment of bone defects, which may be used in clinic in the future.